(untitled) (Federal University Gusau Faculty of Education Journal, 2026)
Primary education reforms remain central to improving educational quality and learning outcomes in Nigeria, yet evidence on their implementation at the local government level is limited. This study assessed the implementation of primary education reforms in public primary schools in Oyo East Local Government Area, Oyo State, Nigeria, with particular focus on the level of implementation, teacher capacity, adequacy of instructional resources, and teachers’ perceptions of reform impact on teaching and learning outcomes. A quantitative survey research design was adopted. The population comprised public primary school teachers in Oyo East Local Government Area, from which a sample of 150 teachers was selected using appropriate sampling techniques. Data were collected using a structured questionnaire and analyzed using descriptive statistics, including frequencies, percentages, mean scores, standard deviations, and correlation analysis. The findings revealed that the implementation of primary education reforms was generally moderate across schools. Teacher capacity was found to have a significant influence on reform implementation, indicating that teachers’ training and professional preparedness play a critical role in translating reform policies into classroom practice. The study also established that instructional resources were largely inadequate, posing a major challenge to effective reform implementation. Furthermore, teachers perceived the impact of primary education reforms on teaching and learning outcomes as moderately positive, suggesting that while reforms have begun to yield benefits, their full potential has not yet been realized. The study concludes that sustained improvement in primary education reform outcomes requires coordinated efforts focused on teacher professional development, adequate resource provision, and strengthened institutional support mechanisms. The findings provide empirical evidence to inform policymakers and education stakeholders on strategies for enhancing primary education reform implementation at the grassroots level